Islamic Youth Participation In The Emergence Of Local Ritual: Encountering The Spirit Of Islam In The Local Tradition - Taufiqurrohim T (Universitas Nahdlatul Ulama Surabaya, 2020)
How Muslim youth encountering local festival is fascinating discourse in the age where the spirit of Islamic revivalism is going on. By this, Dieng Culture Festival is known as one of the popular annual ritual which performs the traditional cultural attraction in Central Java, especially in Banjarnegara and Wonosobo which is heavily rooted on Javanese Hindu tradition. The different perspective of the awareness in considering the Importance of the ritual comes from the diverse community and society to acknowledge this kind of the ritual. So, this paper tries to examine the participation of the youth in enduring the annual festival as one of the events which not only give the advantage for the sustainability of the ritual itself, but also influence to the society around the place economically, socially and spiritually. Through youth participation, this research would try to reveal how youth is significant resource to build multi-cultural community. Using the theory of the “spectacle attraction”, the writer tries to trace how useful the ritual effecting Dieng as one of the wellknown place of the tourism and spiritually affecting to the way of religious life to see the ritual through the direct observation to the place, interview the practitioner of the ritual and the documentation review as the supporting data of the research. Here, I argue that encountering Islam and local tradition has shaped Muslim youth identity in understanding local community and multi-cultural society.